NEURAL STYLE TRANSFER IN ART EDUCATION A CASE STUDY OF DIGITAL CREATIVITY - Saini, Jyoti; Mitra, Bhaskar; Rampal, Sourav; Mahajan, Vibhor; Gavali, Ashwini B; Tewatia, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper is a pedagogical investigation of the Neural Style Transfer (NST) as a means of promoting digital creativity in art education. With the growing influence of artificial intelligence in creative practice, it is up to educators to identify ways of using emerging technologies to facilitate creative expression and not to automate it. The paper presents a case study on how NST may be applied in a formal education setting to enhance students’ knowledge of visual styles, increase their range of creative decisions, and promote experiments in digital media. The study was done using a sample group of undergraduate art students that had gone through a sequence of workshops that were aimed at creating stylized images using the NST algorithms. The qualitative information such as student feedback, notes, and art analysis were gathered to analyze the transformation of creative processes and attitudes toward AI-assisted artmaking. Results have shown that NST has offered a point of access to the world of computational creativity, allowing students to rebuild their own work based on the prism of various artistic styles. The students were found to have been more engaged and more willing to take aesthetic risks, and to have been digital literate. Nonetheless, other issues (i.e. excessive dependence on automated results and lack of knowledge about algorithmic decision-making) are also noted in the study. Comprehensively, the study implies that a well-considered application of NST can become an effective pedagogical means that can enhance the creative exploration and help to cultivate hybrid digital-artistic qualities during art education.